Role of CT scan in evaluation of retroperitoneal lumps - Tandel, Prabhubhai R.; Patel, Himanshu R.; Patel, Kiran U. (International Surgery Journal, 2018)
Background: With the advent and advances in the field of radiological and imaging techniques, the diagnosis of lump can be made with greater accuracy than previous years. The better diagnostic facilities like ultrasonography, computer tomographic scan and magnetic resonance imaging shows mass lesions directly in their entirety. Within two decades of CT scan there have been rapid technical advances, which has provided us with high quality images but at a substantially increased cost. Methods: This is prospective study. It was conducted from June 2017 to July 2018 at GMERS Medical College Valsad. A Study of 25 cases was carried out, after thorough clinical examination and necessary investigations, patients were subjected to CT scan of abdomen. CT Scan was carried out for the extent of the growth, exact nature of the growth and whether growth is respectable or not. Results: The present series of 25 cases of retroperitoneal lump the age of patient varied a lot. Maximum number of cases were seen in fourth, fifth and sixth decades. Symptoms include lump, pain in abdomen and other associated complaints. Conclusions: Definitive diagnosis and precise detail of disease was not obtained by conventional investigations, CT scan was performed in all cases and added information was gained by the same study like inoperable growth, lymph node, metastases, vein or inferior vena cava involvement.